Developing Freshwater Fish Farming to Support Food Security and Alleviate Stunting - Franchy Ch. Liufeto; Stefanus P. Manongga; Markus Bunga; Damianus Adhar (Indonesian Journal of Multidisciplinary Science, 2023)
The large number of stunting cases in the TTS area is caused by a lack of food security. Therefore, the development of freshwater fish farming is very important to support food security and prevent fainting in the region. This is because the fishing industry plays an important role in increasing food security; it also reduces stunting in the region. This study used a cross-sectional research design that observed and measured all variables simultaneously. The research results show that Indonesia has an urgent need to explore the untapped potential of fresh water fish food. This is because increasing their food security and improving their nutrition will help them cope with the country's current situation. One way that can be done is to encourage the use of fish farming foods that are well known to the public, especially foods that are popular among TTS residents.